Determination of Arsenic in Panax notoginseng by Hydride Generation Atomic Fluorescence Spectrometry - Pan, Qingshan; Liu, Wei; Yang, Jin; Min, Yong; Huang, Zhaolong (Asian Journal of Chemistry, 2013)
To determine the total arsenic in Panax notoginseng a hydride generation atomic fluorescence spectrometry method was developed by atomic fluorescence spectrometry (AFS-3100). The samples were pretreated by high pressure digest. The experimental conditions were studied and optimized. There was a good linear relationship between the fluorescence intensity and arsenic concentration in the range of 0-80 μg L-1 with a correlation coefficient of 0.9995, while the detection limit was 0.036 μg L-1, a relative standard deviation of 1.7 % arsenic in the samples was 0.391 μg g-1 and a recovery range of 90.7-103.5 % was obtained.